INTERNET REMOTE LABORATORY SYSTEM (IRLS) - Michta, Emil; Miczulski, Wieslaw; Powroznik, Piotr; Eljasz, Dariusz (International Journal of Computing, 2014)
In the article, the evolution of remote laboratory architectures is presented and the benefits following from the use of an application environment in the form of Web services are pointed out. It is suggested that an education space comprising remote laboratory domains managed by a service broker, co-operating with clients and a laboratory server should be distinguished. A remote metrology laboratory solution is presented.